IMPROVEMENT LED radiation source - and and (Municipal economy of cities (Technical science), 2013)
Based on the experimental study of characteristics of new electric power LEDs AC type "Asriche" as energy-saving light source for lighting equipment for various purposes proposed method improve their functional parameters and developed a scheme that allows increase efficiency LED to almost 100%.